Assessment of the Impact of Fiscal Policy on Economic Growth: An Empirical Analysis - Vijay Varadi; C. Vanlalramsanga (Economics and Econometrics Research Institute (EERI), 2012)
The paper attempted to analyzes linkages between fiscal policies (public expenditure and public debt) and economic growth by investigating the impact of public expenditure and public debt on economic growth (GSDP). To find out empirically the relationship between GSDP and Public Debt, the study analyzes annual time series data from 1987-88 to 2009-10 (BE) having 23 observations. The study results indicated that public expenditure correlates positively to GSDP while public debt correlates negatively to GSDP during the study period. The empirical evidence suggests that debt funded public expenditure does not contribute positively to growth in the State and the state government should preferably avoid accumulation of debt. Further, the debt dynamics indicated that persistent generation of public debt in the state is resulting in mounting debt service burden as debt funded investment does not result in generating assets for economic growth.
Keywords: A11; E21; E27; E61; H5; H30; 330; Debt Dynamics; Economic Growth; Government Expenditure